DESA MENDAHARA TENGAH 2005 – 2024 - Nurhasanah Nurhasanah; Siti Heidi Karmela (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2026)
The purposes of this research are to describe the changes that occurred before and after the development of Mendahara Tengah Village and explain how development changes can have an impact on the lives of residents in Mendahara Tengah Village. This research uses a historical method, this historical method is in accordance with the type of research that the author made, the historical method has several stages, namely heuristics, criticism, interpretation, and historiography. Based on the results of the study, it was found that before the expansion, Mendahara Tengah Village was a village located in the watershed (DAS) of east Tanjung Jabung Regency, Jambi Province. At that time, this village received less attention in development due to its considerable distance from the district capital. It was only after 2005, when the expansion occurred and Mendahara Tengah Village was divided into four villages: Mendahara Tengah Village, Bakti Idaman Village, Sungai Tawar Village, and Merbau Village.